A RETROSPECTIVE STUDY ON AETIOLOGICAL FACTORS, PATIENT CHARACTERISTICS AND TREATMENT PATTERN OF ORAL CARCINOMA- BURDEN OF INDIA - PURUSHOTHAMAN, AISWARYA; P R, ROSHNI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Oral cancer is a burden in the Indian subcontinent and ranks top three types of cancer in the country. It is one of the most fatal health problems faced by the mankind today. Because of cultural, ethnic, geographic factors and also the popularity of addictive habits, the frequency of oral cancer is raising high in India. It ranks number one in terms of incidence among men and third among the women. Various aetiological factors like tobacco and tobacco related products, alcohol, genetic predisposition and hormonal factors are suspected as possible causative factors of oral cancer. Hence the objective of the study was to determine the prevalence, risk factors and treatment pattern of oral carcinoma in a private hospital. It was a retrospective study conducted in the department of Oncology, with a sample size of 337 patients and study duration of 36 months. The data were collected using a standard data collection form. The various sites of oral cancer included in the study are tongue, buccal mucosa, lip, palate, floor of tongue and floor of mouth and retro molar trigone. The objective of our work was to study the current prevalence of oral carcinoma and its clinical characteristics. Keywords: Oral cancer, Surgery, Chemotherapy, Radiotherapy